2014
DOI: 10.1049/iet-rpg.2013.0152
|View full text |Cite
|
Sign up to set email alerts
|

Low‐cost wind resource assessment for small‐scale turbine installations using site pre‐screening and short‐term wind measurements

Abstract: A two-stage approach to low-cost wind resource assessment for small-scale wind installations has been investigated in terms of its ability to screen for non-viable sites and to provide accurate wind power predictions at promising locations. The approach was implemented as a case study at ten UK locations where domestic-scale turbines were previously installed. In stage one, sites were pre-screened using a boundary layer scaling model to predict the mean wind power density, including estimated uncertainties, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Once WS data are fitted to a DM, WP can be assessed. Both GSA [35] [35] performed GSA of WP density of a small-scale onshore WT in the UK with the Sobol method using GUI-HDMR [51]. The SAIVs were regional displacement height, roughness length (RL), blending height, and W2 shape factor.…”
Section: Wind Powermentioning
confidence: 99%
See 1 more Smart Citation
“…Once WS data are fitted to a DM, WP can be assessed. Both GSA [35] [35] performed GSA of WP density of a small-scale onshore WT in the UK with the Sobol method using GUI-HDMR [51]. The SAIVs were regional displacement height, roughness length (RL), blending height, and W2 shape factor.…”
Section: Wind Powermentioning
confidence: 99%
“…The relationship between the WS and WP is known to be cubical (8) [25], so whenever the WS or its DM parameters are present among SAOVs, OAT is not acceptable. Numerous attempts at quantifying the uncertainty in WP associated with the WS were made [35]- [45][44], some -with OATSA [43][45] [44]. He et al [45] sharply observed that all relationships between SAIVs (WS threshold, slope threshold, elevation threshold, and bathymetry threshold) and the SAOV were nonlinear, but used OATSA nonetheless.…”
Section: Wind Powermentioning
confidence: 99%
“…ω s = 2πf s is the angular frequency of the operating frequency f s . Equations (5)- (7) show the corresponding expressions of these three resonant points. If the imaginary part V ImC is set to zero, the expressions of resonant points f C1 and f C3 can be acquired, as shown in Equations (5) and 7, respectively.…”
Section: Characteristic Analysis For the Cltcl Circuitmentioning
confidence: 99%
“…Wind power, as an important form of new energy power generation, has attracted much attention [1][2][3][4]. Compared to the large and medium-scale wind power generation systems (WPGSs) [5], small-scale WPGSs have the advantages of lower cost, more flexible installation and a higher utilization rate of wind energy [6][7][8][9]. Moreover, they can be divided into off-grid and grid-connected WPGSs [10].…”
Section: Introductionmentioning
confidence: 99%
“…LMSWTs are typically part of hybrid off-grid systems, with installed capacity of renewable energy sources of up to 10 kW, while their rotor diameters range from 1.2 to 6 m, producing power from 200 W to 5 kW, respectively, at 10 m/s wind speeds. These small wind turbines are typically direct drive, unlike larger small wind turbines [11] which utilise a gearbox, variable speed machines which consist of a three blade wooden [12,13] horizontal axis rotor of constant pitch angle, of a coreless axial flux permanent-magnet generator (AFPMG) [14] with a double rotor single stator configuration and utilise a passive gravity furling tail system for rotor speed regulation. The use of AFPMGs is typical for these small-scale wind energy applications [15][16][17], mostly due to the simple manufacturing techniques required for constructing the stator and the rotor of the machine.…”
Section: Introductionmentioning
confidence: 99%